Back Cover: [NMe4][I4Br5]: A new Iodobromide from an Ionic Liquid with Halogen–Halogen Interactions (Chem. Eur. J. 2/2017). Issue 2 (5th December 2016) - Mann, Lisa; Voßnacker, Patrick; Müller, Carsten; Riedel, Sebastian
Abstract : The tetraiodopentabromide anion [I4 Br5 ] − shows a different stereochemistry depending on the type of solvent used to crystallize it. This contrastive relationship is illustrated with a yin–yang drawing; the Dead Sea (yang) represents the ionic liquid [HMIM][Br] from which the syn ‐[I4 Br5 ] − anion was crystallized. The Mediterranean Sea (yin) represents an organic solvent, dichloromethane, from which the anti ‐[I4 Br5 ] − anion was isolated. Both isomers were characterized by single‐crystal X‐ray diffraction, Raman spectroscopy and quantum chemical calculations. More information can be found in the Communication by S. Riedel et al. onpage 244 ff.